2016
DOI: 10.3109/08820139.2016.1157814
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Attenuates LPS-induced Acute Lung Injury through Inhibition of NF-κB, COX-2, and Pro-inflammatory Mediators

Abstract: Dexamethasone (DEX) is a synthetic glucocorticoid with potent anti-inflammatory effects that is widely used to treat inflammatory diseases. The aim of the present study was to investigate the possible protective effect of DEX on the lipopolysaccharides (LPS)-induced acute lung injury (ALI) in a mouse model. Animals were pretreated with DEX (5 and 10 mg/kg, i.p.) for seven days and acute lung injury was induced by intranasal (i.n.) administration of LPS on day 7. In the present study, administration of LPS resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 74 publications
0
49
0
1
Order By: Relevance
“…Animal model studies have demonstrated that DEX administration decreased lung tumor incidence in tobacco smoke‐exposed mice, and potentiates the effect of chemotherapeutic drugs . As an anti‐inflammatory drug, DEX is known to control the endotoxin‐induced lung inflammation and inflammatory cytokines . Clinical trial studies have shown the beneficial role of DEX in septic shock or systemic inflammatory condition .…”
Section: Introductionmentioning
confidence: 99%
“…Animal model studies have demonstrated that DEX administration decreased lung tumor incidence in tobacco smoke‐exposed mice, and potentiates the effect of chemotherapeutic drugs . As an anti‐inflammatory drug, DEX is known to control the endotoxin‐induced lung inflammation and inflammatory cytokines . Clinical trial studies have shown the beneficial role of DEX in septic shock or systemic inflammatory condition .…”
Section: Introductionmentioning
confidence: 99%
“…During the early stage (0–3 days) of adipogenic differentiation, the expression of multiple proinflammatory cytokines (e.g., IL‐1β, IL‐6, IL‐8, and CCL2) dramatically decreases, which might contribute to suppression of NF‐κB and ERK1/2 pathways, as both can positively regulate proinflammatory cytokines (Al‐Harbi et al, ; Chen et al, ). Dexamethasone in adipogenic medium is a strong inhibitor of NF‐κB (Laberge et al, ; Al‐Harbi et al, ). In the present study, inhibition of the ERK1/2 pathway was detected by a Western blot, although the source of this inhibition was not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, dexamethasone completely prevented TNF-induced SIRS, but was no longer protective when given 6h-8h after TNF challenge, suggesting the establishment of a quick GC resistance after TNF [119]. Also in numerous other models of acute, lethal inflammation, GCs protect when given in a close time frame compared to the challenge [170][171][172]. The protective power of GCs in pre-clinical sepsis models is less spectacular, but still significant.…”
Section: Gcr In Sepsismentioning
confidence: 91%